Description and Dynamics of the Santos Bifurcation - Braga, Agata Piffer (2019)
In this study we describe the Santos Bifurcation mean pattern and investigate its modal composition. Also we analyze and compare the local water masses transports for the Santos Bifurcation split, in terms of annual and intraseasonal means. The Santos Bifurcation is crucial to the understanding of the Brazil Current system and it is located in a important oil and gas exploration blocks domain, what increases even more the demands of environmental control in the region. In order to answer our questions we validated the Mercator Global model output with quasi-synoptic data from the OSE Brazilian Navy cruise. The results shown virtually constant position of the bifurcation occurrence over time, although the split transport presented variations. During May and June the northern branch volume transport is higher, representing around 68% of the sum. During the October and November months, the split reaches its most discrepancy, when the southern branch is responsible for more than 74% (more than 2/3) of the sum. In the other months, despite the transport of the southern branch is higher, it corresponds to 50-60% of the sum. Regarding the modal composition we have found that the south South Equatorial Current is essentially barotropic, and its first and second baroclinic modes have less than 3.5% of explained variance. On the other hand, in the Brazil Current system the baroclinicity increases equatorward, changing from 2.84, South of the bifurcation, up to 34%, north of the bifurcation, of explained variance. This is the first tridimensional description of the Santos bifurcation, and its transport variability.